2021
DOI: 10.20944/preprints202104.0633.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Hierarchical Framework for Assessing Transmission Causality of Respiratory Viruses<strong> </strong>

Abstract: We propose a hierarchical framework based on our experience of systematically reviewing and synthesizing 378 primary studies for an evidence-based update of the modes of transmission for SARS-CoV-2. These studies revealed significant methodological shortcomings with a lack of standardization in the design, conduct, testing and reporting of SARS-CoV-2 transmission. While this situation is in part excusable at the outset of a pandemic, evidence rules of proof for assessing the transmission of this virus are need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The Ct values were lowest in fomite samples from two studies [12,19] that included participants receiving either high-flow oxygen or mechanical ventilation: 22.3 to 29.7, and 23 to 26, respectively. A third study [32], including participants on oxygen, reported higher Ct values (35)(36)(37)(38)(39)(40); however, the investigators noted that participants in the high-flow nasal oxygen (HFNO) group were sampled significantly later in their illness compared to those receiving only supplemental oxygen: mean 16-days vs mean 9 days, J o u r n a l P r e -p r o o f from symptom onset, respectively. The authors of one study of SARS-CoV-2 patients in acute care [23] reported that hypoxia on admission (P=0.003), Ct ≤30 on or after the sampling date (P=0.006), higher Charlson comorbidity index score (P=0.002), and shorter time from illness onset (<7 days) to sampling date (P=0.02) were significantly associated independent risk factors for positive SARS-CoV-2 PCR tests from fomite samples.…”
Section: Sars-cov-2 Pcr Results In Fomite Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ct values were lowest in fomite samples from two studies [12,19] that included participants receiving either high-flow oxygen or mechanical ventilation: 22.3 to 29.7, and 23 to 26, respectively. A third study [32], including participants on oxygen, reported higher Ct values (35)(36)(37)(38)(39)(40); however, the investigators noted that participants in the high-flow nasal oxygen (HFNO) group were sampled significantly later in their illness compared to those receiving only supplemental oxygen: mean 16-days vs mean 9 days, J o u r n a l P r e -p r o o f from symptom onset, respectively. The authors of one study of SARS-CoV-2 patients in acute care [23] reported that hypoxia on admission (P=0.003), Ct ≤30 on or after the sampling date (P=0.006), higher Charlson comorbidity index score (P=0.002), and shorter time from illness onset (<7 days) to sampling date (P=0.02) were significantly associated independent risk factors for positive SARS-CoV-2 PCR tests from fomite samples.…”
Section: Sars-cov-2 Pcr Results In Fomite Samplesmentioning
confidence: 99%
“…Evidence for a chain of transmission of SARS-CoV-2 from fomites to humans was not reported in the studies reviewed. Nonetheless, a chain of transmission was demonstrated by SARS-CoV-2 from respiratory tract specimens which can deposit on “fomites” that can survive for many hours and can readily cause invasive infection in the Syrian hamster model l[ 24 ] at very low infecting doses [ 37 ], fulfilling both the Gwaltney-Hendley postulates of viral causation and Koch’s postulates [ 38 ]. These very low infectious doses are consistent with the recently published human challenge experiments demonstrating infection in 53% using an inoculum of only 10 TCID50 (∼7PFU) in 0·1 mL of a wild-type virus (SARS-CoV-2/human/GBR/484861/2020) [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…10 Although the dataset was limited, we observed an inverse relationship (Ct/Cq) or direct relationship (log copies): the viral burden indicated by these methods correlated with infectiousness, as shown by the ability to produce replication-competent virus in culture. The presence of replication-competent virus reflects one of the highest grades of evidence supporting the capability for forward transmission of SARS-CoV-2 16,17 .…”
Section: Results Of the Studiesmentioning
confidence: 99%